2004
DOI: 10.1159/000075650
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Respiratory Therapist-Directed Protocol on Prescription and Outcomes of Pulmonary Rehabilitation in COPD Inpatients

Abstract: Background: The use of respiratory therapist-directed (RD) protocols in non-ICU hospitalized patients decreases respiratory care charges as compared with physician-directed (PD) protocols. Objectives: To determine whether RD or PD protocol assessments in COPD patients may impact: (1) prescription of respiratory treatments, and (2) outcomes of pulmonary rehabilitation program (PRP). Methods: In a retrospective observational case-control study, 73 cases (RD) were compared with controls (PD) matched for age, sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Our PR was a hospital-based, inpatient, multidisciplinary program, held in 18 consecutive sessions, which had been previously described [13, 14]; each session included both endurance and strength training of the limbs. Briefly, it included the optimization of pharmacologic treatment, endurance training delivered in order to achieve 70–80% of the maximal load reached at the baseline test, upper and lower limbs’ muscle strength exercises lifting weights (increased gradually from 300 to 1,000 g, based upon the ability to reach 10 consecutive repetitions), twice weekly disease education sessions as well as behavioral, nutritional and psychosocial counseling.…”
Section: Methodsmentioning
confidence: 99%
“…Our PR was a hospital-based, inpatient, multidisciplinary program, held in 18 consecutive sessions, which had been previously described [13, 14]; each session included both endurance and strength training of the limbs. Briefly, it included the optimization of pharmacologic treatment, endurance training delivered in order to achieve 70–80% of the maximal load reached at the baseline test, upper and lower limbs’ muscle strength exercises lifting weights (increased gradually from 300 to 1,000 g, based upon the ability to reach 10 consecutive repetitions), twice weekly disease education sessions as well as behavioral, nutritional and psychosocial counseling.…”
Section: Methodsmentioning
confidence: 99%
“…4,7,8 In addition, Tramacere et al 11 showed that RT delivered by protocol results in more timely implementation of therapy. To our knowledge, no previous studies have addressed the effect of therapist-directed protocols on 30-d readmission rate and hospital stay for COPD subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, protocol RT results in more timely therapy than non-protocol RT. 11 This study addresses the effectiveness of protocol RT in COPD subjects admitted for exacerbations of their disease. Although Tramacere et al 11 studied the effectiveness of therapist-directed protocols in COPD in-patients, they focused on pulmonary rehabilitation outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] EBP has been proposed as a useful means to improve healthcare outcomes for RTs. [8][9][10][11] Therefore it is essential to assess how RTs implement EBP in clinical decision-making. A number of studies have illustrated that, although a majority of medical, nursing, pharmacologic, and allied health professions hold positive attitudes toward EBP, their knowledge and skill pertaining to EBP implementation are relatively insufficient.…”
Section: Introductionmentioning
confidence: 99%